Barriers to cervical cancer prevention in rural Cameroon: a qualitative study on healthcare providers’ perspective - Pierre Vassilakos; Bruno Kenfack; Patrick Petignat; Jessica Sormani; Ania Wisniak; Nicole Schmidt; Amandine Noemie Roux; Alexandre Ndjalla; Karoline Tatrai (BMJ Open, 2021)
Objective Cervical cancer in Cameroon ranks as the second most frequent cancer among women and the leading cause of cancer-related deaths, mainly due to the lack of prevention. Our principal objective was to explore potential barriers to an human papillomavirus (HPV)-based cervical cancer screening from a healthcare provider (HCP) perspective in a low-income context. Second, we aimed to explore the acceptability of a single-visit approach using HPV self-sampling.Settings The study took place in the District hospital of Dschang, Cameroon.Participants Focus groups (FGs) involved HCPs working in the area of Dschang and Mbouda.Primary and secondary outcome measures All FGs were audiorecorded, transcribed and coded independently by two researchers using the ATLAS.ti software. A qualitative methodology was used to capture insights related to the way people perceive their surroundings. Discussion topics focused on perceived barriers, suggestions to improve cervical cancer screening uptake, and acceptability.Results A total of 16 HCPs were interviewed between July and August 2019. The identified barriers were (1) lack of basic knowledge on cervical cancer among most women and men and (2) lack of awareness of the role and existence of a screening programme to prevent it. Screening for cervical cancer prevention using HPV self-sampling was considered as an acceptable approach for patients according to HCPs. Traditional chiefs were identified as key entry points to raise awareness because they were perceived as essential to reach not only women, but also their male partners.Conclusions Awareness campaigns about cervical cancer, its prevention and the availability of the screening programmes are crucial. Furthermore, involving male partners, as well as key community leaders or institutions was identified as a key strategy to encourage participation in the cervical cancer screening programme.Trial registration Ethical Cantonal Board of Geneva, Switzerland (CCER, N°2017-0110 and CER-amendment n°2) and Cameroonian National Ethics Committee for Human Health Research (N°2018/07/1083/CE/CNERSH/SP).